Citizens’ Perceptions of Codeswitching in Public Communication in Rwanda - Celestin Ryaziga (Social Empowerment Journal, 2025)
Noticing the frequent codeswitching practices in political communication in Rwanda, this study was conducted to investigate the Rwandan citizens’ perceptions of this linguistic phenomenon in public communication. The study’s objectives were to examine whether the practices of codeswitching affect the citizens’ understanding, to investigate citizens’ perceptions of codeswitching and to raise awareness among Rwanda’s government leaders about this linguistic phenomenon. In order to make it comparative, this study was conducted in two distinct areas: Huye city as urban area and Gisagara district as a rural area. The number of participants was 44: 22 urban citizens and 22 rural citizens. Moreover, a mixed methodology was employed, combining group discussions to collect qualitative data and semi-structured interviews using a questionnaire. The study was accomplished through descriptive statistical analysis of codeswitching. The findings reveal that many Rwandan citizens view codeswitching practices unfavourably for it hinders them from fully understanding the public communication.  Comparatively, the study found that codeswitching hinders rural citizens’ ability to comprehend public communication more than it does for urban citizens. Based on these findings, this study recommends government leaders to prioritize the use of Kinyarwanda while delivering public communication. It also further recommends the government of Rwanda to organise regular training sessions for all government leaders to raise their awareness of the effect of codeswitching. In recognition that codeswitching is an inevitable linguistic phenomenon (Nilep, 2006:1), this study recommends that Rwandan government leaders provide translations whenever codeswitching occurs in public communication.